Meningkatkan Konsentrasi Anak Gangguan Spektrum Autisme dengan Media lego Brick - Khairani, Salsabila; Rahmahtrisilvia, Rahmahtrisilvia (Universitas Negeri Padang, 2024)
The focus on the problems faced by children with autism spectrum disorders (ASD) in class II SLB was the driving force for this research. The aim of this research is to find out whether Lego Brick media helps class II students at SLBN 2 Padang with Autism Spectrum Disorder focus better. With design A–B, this research uses a Single Subject Research (SSR) experimental research design. Documentation, duration instruments, and observation are the methods used to collect data. Visual graphs are used to assess data in two ways: within conditions and between conditions. Analysis of research data produced results from twelve meetings. The mean level is 4.5, the highest limit is 4.9, the lower limit is 4.1, the percentage is 0, and the stability trend is in the stability range of 0.75 in baseline conditions (A). A stability range of 1.2, a mean level of 6.3, an upper limit of 6.9, a lower limit of 5.7, and a stability percentage of 50% were observed in the intervention condition (B). Based on research findings, it can be said that children with autism spectrum disorders can become more focused when using Lego Brick media.